The antifibrotic drug halofuginone reduces ischemia/reperfusion-induced oxidative renal damage in rats - YEGEN, BERRAK; KARADENİZ CERİT, KIVILCIM; YÜKSEL, MERAL; ÖZKAN YENAL, NAZİYE; ÇETİNEL, ŞULE (ELSEVIER SCI LTD, 2013)
Aim: The objective of the present study was to evaluate the protective effects of halofuginone against renal ischemia/reperfusion (I/R) injury. Materials and methods: Male Wistar albino rats were unilaterally nephrectomized and the left renal pedicles were occluded for 45 min to induce ischemia and then reperfused for 6 h (early) or for 72 h (late). The rats were treated intraperitoneally with either halofuginone (100 mu g/kg/day) or saline 30 min prior to ischemia and the dose was repeated in the late reperfusion groups. In the sham groups, rats underwent unilateral nephrectomy and were treated at similar time points. The animals were decapitated at either 6 h or 72 h of reperfusion and trunk blood and kidney samples were obtained. Results: I/R injury increased renal malondialdehyde levels, myeloperoxidase activity and reactive oxygen radical levels, and decreased the renal glutathione content. Halofuginone treatment was found to reduce oxidative I/R injury and improve renal function in the rat kidney, as evidenced by reduced generation of reactive oxygen species, depressed lipid peroxidation and myeloperoxidase activity, and increased glutathione levels. Conclusions: The present findings demonstrate the anti-inflammatory and antioxidant effects of halofuginone in renal I/R injury, supporting its potential use where renal I/R injury is inevitable. (C) 2012 Journal of Pediatric Urology Company. Published by Elsevier Ltd. All rights reserved.
Keywords: Halofuginone; Ischemia/reperfusion; Acute renal injury; Oxidant damage; Rat; ISCHEMIA-REPERFUSION INJURY; EXTRACELLULAR-MATRIX DEPOSITION; COLLAGEN TYPE-1 SYNTHESIS; I SYNTHESIS; COCCIDIOSTAT HALOFUGINONE; CELL-PROLIFERATION; INHIBITOR; FIBROSIS; MELATONIN; GROWTH